The relationship between body fat percentage and body mass index in overweight and obese individuals in an urban african setting - Mukadas O. Akindele; Julie S. Phillips; Ehimario U. Igumbor (AOSIS, 2016)
The increase in the prevalence of overweight and obesity in both developed and developing countries is associated with musculoskeletal and other non-communicable diseases. To address this, an accurate measure of body adiposity, bearing in mind several shortcomings of body mass index (BMI), should be used. This study determined the relationship between BMI and body fat (BF)% among adult Nigerians of different ethnic groups residing in an urban setting. Using multistage cluster sampling technique were recruited 1571 subjects (>18 years; male=51.2%) in a cross-sectional study. Body adiposity indices were assessed using BMI and BF%. Using BF%, the result shows that a total number of 156 (9.9%) had low BF% while 291 (18.5%) had very high BF%, while the BMI classifications of body adiposity, 68 (4.3%) were underweight while 271 (17.3%) were obese. There was a strong and positive statistical relationship between BF% and BMI when both were paired without controlling for gender and age (r=0.81, P<0.01). The results show that there is a strong positive association between BMI and BF%, and age and sex are predictors of this association.